Online Reciprocal Teaching and Its Impact on Islamic University Students’ Reading Comprehension in Standardized Testing - Hidayat, Hendi; Waloyo, Edy; Priajana, Nana (UIN Salatiga, 2025)
In an era where literacy serves as a gateway to global participation, many Muslim EFL learners continue to encounter significant challenges in mastering academic reading skills. This study investigate the effectiveness of Online Reciprocal Teaching (ORT) versus Online Reading Strategy Instruction (ORSI) in enhancing reading comprehension among Muslim learners in standardized English proficiency tests. The participants consisted of 74 fourth-semester students enrolled in a fully online English course at UIN Siber Syekh Nurjati Cirebon. A pre-test post-test control group design was employed, with Class A (n = 37) receiving ORT intervention, which focused on predicting, questioning, clarifying, and summarizing, while Class B (n = 37) received ORSI instruction emphasizing skimming, scanning, and making inferences. The intervention spanned 16 sessions, delivered through a blend of live and recorded formats. Reading comprehension was assessed using a validated test adapted from the Longman Preparation Course for the TOEFL. Pre-test scores were treated as covariates in the ANCOVA analysis. The results revealed a statistically significant improvement in the post-test scores of ORT group compared to the ORSI group. These findings suggest that reciprocal teaching fosters deeper cognitive and metacognitive engagement in online reading instruction. The study recommends the integration of ORT into EFL curricula at Islamic higher education institutions to support more inclusive, strategic, and effective learning practices.